ОҢТҮСТІКТЕН СОЛТҮСТІККЕ ҚОНЫС АУДАРУ: ІШКІ КӨШІ-ҚОНДЫ БАСҚАРУ МӘСЕЛЕЛЕРІ - Ykylas, M.; Gabdulina, B. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2022)
According to forecasts of national experts, the population of the country will amount to 24.5 million people by 2050. Considering that currently the majority of the country's population is concentrated in the southern regions, this trend is unlikely to change in the near future. That is, regional disparities and demographic imbalance have long been formed in the country (photo 1). Special programs have been adopted at the State level to restore this imbalance. Work has begun on the resettlement of people from densely populated southern regions to northern regions where there is not enough labor. Since the beginning of the program, about 20 thousand people have moved to the north from the south of the country. There are special incentives that will be provided as material, financial assistance to those who move to the northern regions. Despite the fact that the application for relocation under the program is facilitated to a minimum for a new place, the first results of this internal migration remain disappointing so far. Consequently, the state program aimed at increasing internal migration has both pros and cons. The article discusses ways to eliminate shortcomings, along with the effective sides of this internal migration and an attempt to find answers to the questions that have arisen on internal migration.